2014
DOI: 10.1371/journal.pone.0098202
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Hemoglobin Levels by Anti-IL-6 Receptor Antibody (Tocilizumab) in Rheumatoid Arthritis

Abstract: ObjectiveTo compare the effect of tocilizumab (TCZ) with other biologic therapies in improving anemia of rheumatoid arthritis (RA) patients.MethodsWe compared the change of hemoglobin (Hb) levels in a cohort of 147 consecutive RA patients who were treated with biologics for more than 12 weeks. Twenty eight patients were treated with TCZ, and 119 patients were treated with biologics other than TCZ (87 with TNF inhibitors and 32 with abatacept). The change of Hb levels from baseline to week 12 was compared betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 26 publications
(41 reference statements)
2
30
1
1
Order By: Relevance
“…Although, baseline levels of the CD45R0 + CD26 - subset were not recovered with any of the therapies at the time of sampling, a correlation with hemoglobin levels was observed in the anti-IL-6R group. IL-6, together with TNF- α [ 35 ], is an inflammatory cytokine critically involved in chronic disease´ anemia, the major reason for the low hemoglobin levels in RA patients. In fact, it has been recently reported that hemoglobin levels increase after biologic therapies, mainly with anti-IL-6R [ 35 ], indicating that anti-IL6R therapy could lead to the recovery of this population.…”
Section: Discussionmentioning
confidence: 99%
“…Although, baseline levels of the CD45R0 + CD26 - subset were not recovered with any of the therapies at the time of sampling, a correlation with hemoglobin levels was observed in the anti-IL-6R group. IL-6, together with TNF- α [ 35 ], is an inflammatory cytokine critically involved in chronic disease´ anemia, the major reason for the low hemoglobin levels in RA patients. In fact, it has been recently reported that hemoglobin levels increase after biologic therapies, mainly with anti-IL-6R [ 35 ], indicating that anti-IL6R therapy could lead to the recovery of this population.…”
Section: Discussionmentioning
confidence: 99%
“…These 2 laboratory measurements are known to increase with IL6R antagonist therapy. 5,[22][23][24][25][26] The known reduction in CRP level was observed in the PheWAS, as were findings consistent with a reduced risk of ischemic heart disease, lower levels of troponin I, and lower CK-MB levels ( Table 3).…”
Section: Association Of Il6r Variant With Laboratory Findingsmentioning
confidence: 89%
“…However, hemoglobin is not considered to be a readily available acute phase response biomarker, unlike ESR and CRP, which are routinely used to estimate the activity of systemic inflammation. Previous studies reported that the hemoglobin level was increased after starting targeted rheumatoid arthritis treatment (22,23), but failed to report longitudinal changes in composite disease activity indices (23). To the best of our knowledge, there are no studies on the direct association between hemoglobin and SLE.…”
Section: Sle Patients (N=212)mentioning
confidence: 95%